DEMAN FOR CHEMICAL FERTILIZER OF THE TECHNICAL IRRIGATION PADDY IN EAST OGAN KOMERING ULU - Munajat, Munajat (Economic Journal of Emerging Markets, 2011)
This research investigates factors that influence demand for chemical fertilizer of the technical irrigation paddy in East Ogan Komering Ulu Regency. Using a multiple regression analysis, the result shows that the significant factors influencing the urea fertilizer demand are the price of urea fertilizer and the previous paddy production. It also finds that the price of paddy and total member of family do not significantly influence the fertilizer. Meanwhile the significant factors that influence the SP 18 fertilizer demand are the price of SP 18 fertilizer, the price of paddy and the previous paddy production. Keywords: Urea fertilizer demand, SP 18 fertilizer demand, fertilizer subsidy JEL classification numbers: O13, 018